PERILAKU NARSIS SOPHIE DALAM NOVEL THE SCHOOL FOR GOOD AND EVIL KARYA SOMAN CHAINANI: SUATU ANALISIS KARAKTER - KIRSTEN, PAKASI KAREN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Upon the title â€œPerilaku Narsis Sophie dalam Novel The School for Good and Evil karya Soman Chainani: Suatu Analisis Karakterâ€ this study analyze the narcissistic behavior of Sophie in the story. Sophie as one of the main character in The School for Good and Evil (2013). Sophie is a beautiful girl who shows traits of narcissists. How is Sophieâ€™s narcissist potrayed through the novel and how does Sophieâ€™s narcissist affect other characters are the problem of this research. Thus, the objective of this research is to identify and analyze Sophieâ€™s narcissistic behavior and to analyze and potrayÂ howâ€™s Sophieâ€™s narcissistic behavior affect other characters. The purpose of this research is to describe the behavior of narcissistic which Sophie possessed. The data were taken by reading the novel, then identifying, classifying and categorizing them. This research uses objective theory from the book of The Mirror and the Lamp (1976) byÂ M.H. Abrams and uses Edgar V. Roberts (1964) theory of character. The data that has been obtained are analyzed by using an intrinsic approach. The intrinsic approach will be used to analyze Sophie narcissisticÂ behavior and her interactions with other characters in this novel. The result of this research conveys that Sophieâ€™s narcissistic behavior shows that the lack of empathy and loving herself excessively lead her to her own destruction and itâ€™s affect other characters to alienated her. As the effect of Sophieâ€™s narcissists towards other characters is differ with each other. The result is having positive and negative effect to the other characters. Â Keywords: Behavior, Narcissistic, The School for Good and Evil, Character Analysis.